2010
DOI: 10.4185/rlcs-65-2010-919-561-571-en
|View full text |Cite
|
Sign up to set email alerts
|

Internet Uses and parental mediation in adolescents with ADHD

Abstract: Abstract:The youth of today lives in the midst of a technological revolution, particularly in the field of communications (e-chats, mobile telephones, Messenger, etc.). In many parts of Spain, the Internet has overtaken television, not only as a source of entertainment and recreation among teenagers, but also as a socialisation force. Adolescents suffering from Attention-Deficit Hyperactivity Disorder (ADHD) have specific characteristics that may make them more vulnerable when using new technologies. Consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 10 publications
0
17
0
1
Order By: Relevance
“…Such a future direction is important because there is research evidence that parents utilize different parental mediational strategies for ADHD versus non-ADHD adolescents (Arrizabalaga-Crespo et al, 2010). Adolescents with ADHD reported that their parents used more restrictive and instructive mediational strategies for their technology use than adolescents without ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Such a future direction is important because there is research evidence that parents utilize different parental mediational strategies for ADHD versus non-ADHD adolescents (Arrizabalaga-Crespo et al, 2010). Adolescents with ADHD reported that their parents used more restrictive and instructive mediational strategies for their technology use than adolescents without ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate the important role of co‐viewing mediation and instructive mediation in buffering against the consequences associated with cyberbullying victimisation. Co‐viewing mediation and instructive mediation might be parental mediation strategies that involve social support, though co‐viewing mediation might offer lower levels of this support (Arrizabalaga‐Crespo et al ., ). Social support has been implicated as exerting a buffering effect on the depression and anxiety that result from a variety of negative experiences in adolescents' lives, including online and offline victimisation (Cheng et al ., ; Ybarra et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Overprotective parents also parent through fear, which could leave their children vulnerable to negative online experiences, particularly cyberbullying victimisation (Clarke et al ., ; Lereya et al ., ). Although parents who utilise co‐viewing mediation do not typically discuss content, they frequently utilise digital media content with their children and it might be likely that they occasionally discuss appropriate content and ways to deal with such content (Arrizabalaga‐Crespo et al ., ). This minimal amount of intervention from one's parents might reduce adolescents' vulnerability to cyberbullying victimisation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations